The Effect of Leg Elevation on Preload Responsiveness in Heart Failure Patients - Mutia Annisa; Tuti Herawati; Amelia Kimin; Agung Waluyo (GLOBAL HEALTH SCIENCE GROUP, 2026)
Accurate hemodynamic assessment is critical for guiding fluid therapy and avoiding fluid overload in patients with heart failure (HF). Leg elevation maneuvers, including passive leg raising (PLR) and leg lifting (PLL), have emerged as functional diagnostic interventions. Still, their multifaceted roles across different HF phenotypes have not been fully synthesized. This literature review aimed to evaluate the effect of leg elevation on preload responsiveness and its broader clinical applications in adult patients with HF. A comprehensive search of online studies published between 2019 and 2025 was conducted across multiple databases (Sage Journals, Scopus, ScienceDirect, PubMed, Wiley Online Library, and ProQuest). Keywords included “heart failure”, “passive leg raising”, and “hemodynamics.” A total of 1551 articles were identified, and 5 articles were thoroughly reviewed. Five articles that met the inclusion criteria were systematically analyzed to synthesize evidence on the impact of PLR on key hemodynamic parameters. Leg elevation serves distinct, context-dependent roles. PLR/PLL is a provocative test in patients with suspected HF with preserved ejection fraction (HFpEF), confirming latent diastolic dysfunction with a significant PCWP increase. A blunted increase in the stroke volume index (SVi) during PLR/PLL signifies exhausted preload reserve and is an independent predictor of poor clinical outcomes in patients with HF with reduced ejection fraction (HFrEF). A significant decrease in PPV during the maneuver accurately predicts fluid responsiveness, which is particularly crucial for vulnerable patients, such as those with heart failure, as it remains accurate even with low-tidal-volume ventilation. Leg elevation is a versatile and reliable non-invasive maneuver with a multifaceted role in the management of HF. Beyond simply predicting fluid responsiveness, it functions as a crucial diagnostic tool for HFpEF, a prognostic tool for HFrEF, and an accurate predictor of fluid needs in critical care settings. Integrating PLR/PLL into clinical practice allows for precise, physiology-based decision-making, fluid management optimization, and improved patient outcomes.